INFLASI INDONESIA DALAM PANDANGAN PHILLIPS CURVE - Nawatmi, Sri (Proceeding SENDI_U, 2015)
This research want to anlysis about inflation in Indonesia by use New Keynesian Philllips Curve.Analysis tool in this research is Vector Autoregressive (VAR), specifically VECM (Vector ErrorCorrection Model). VECM is a type of restrictive VAR to first determine endogenous variablesand exogeneous variable on the theory.Based on the regression results indicate that the ErrorCorrection Term (ECT) is significantly negative (-0.675167). It means that there is the existenceof the error term and the negative sign indicates an error capable of leading to equilibrium.Based on VECM calculation,expected inflation affect on inflation in Indonesia(-0.913099).Indonesia output gap have positive effect (62.98311) while world output gap does not affectinflation in Indonesia. It means that more domestic factors determining inflation in Indonesia ofthe foreign factors.Thus, Bank Indonesia as monetary authorities will be easier to create a policyto govern inflation because domestic factors are easier to control than the foreign factors.Key words: inflation, VAR, VECM, Phillips Curve, New Keynesian, output gap.